The Universe, Life and Everything...Dialogues on our Changing Understanding of Reality - Durston, Sarah (Amsterdam University Press, 2017)
The way we understand the world we live in is changing. Our traditional understanding is being challenged by developments in physics, including quantum mechanics, and our inability to explain certain complex phenomena such as consciousness. In this book, scholars from a variety of backgrounds discuss how our understanding of our world is expanding to include such phenomena.